Hubungan Kecanduan Media Sosial dengan Perilaku Prokrastinasi Akademik pada Siswa Sekolah Menengah Pertama - Natalie, Eva Cahyani; Ides, Stefanus Andang (Lontara Journal of Health Science and Technology, 2026)
The rapid development of technology every year causes internet usage activities in Indonesia to continue to increase. This is also caused by the availability of various social media platforms that hurt students, one is social media addiction which can interfere with students concentration and study time. This study aims to determine the correlation between social media addiction and academic procrastination behavior in students at SMPN 21 Bekasi. Quantitative descriptive research with a cross-sectional approach. The sample in this study were students in grades VII and VIII totaling 97 people and using purposive sampling technique. The research was at SMPN 21 Bekasi in November 2024. The research used a questionnaire distributed via google form with the kendall tau b statistical test. The results of this study show that students are addicted to high social media (54,6%) and moderate academic procrastination behavior (52,6%). There is a correlation between social media addiction and academic procrastination behavior in students at SMPN 21 Bekasi with a p-value of 0.000 < (0.005). It is hoped that students can control themselves, reduce their use of social media, and try to manage their time in academic or non-academic activities. This can help them reduce their level of social media addiction and academic procrastination.